Quantum interaction : 10th International Conference, QI 2016, San Francisco, CA, USA, July 20-22, 2016, Revised selected papers /: 10th International Conference, QI 2016, San Francisco, CA, USA, July 20-22, 2016, Revised selected papers. (2017) - Unknown
No abstract available